Rekonstruksi Kurikulum Pendidikan: Sebuah Analisis Filsafat untuk Membangun Kreativitas Siswa - Said, Khairuddin; Aqodiah, Aqodiah (Ibtida'iy : Jurnal Prodi PGMI, 2024)
The purpose of writing this scientific article is to find out about the reconstruction of the educational curriculum: a philosophical analysis to build student creativity. Reconstructing the educational curriculum is an important effort to adapt the education system to the demands of the ever-evolving times. This paper aims to provide an analytical philosophy in the context of curriculum reconstruction, with a focus on building student creativity. The philosophical approach provides a theoretical basis for understanding the essence of education and the role of creativity in the learning process. This analysis includes an in-depth understanding of the principles of educational philosophy, such as human essence, educational goals, and views on knowledge. The philosophies of existentialism and progressivism are the main conceptual frameworks that encourage student empowerment to develop their creative potential. Thus, it is hoped that the reconstruction of the educational curriculum based on philosophical analysis can create a generation of students who are not only skilled in terms of knowledge, but also have the ability to think creatively and innovatively in facing future challenges.